Uncontrolled Hypertension among Older Hypertensive Patients and Their Drug Adherence Pattern - K. Umakalyani; Kavinilavu Chandrasekaran; S. Dhinagaran; Niveditha Shanmugam (Journal of the Indian Academy of Geriatrics, 2025)
Background: Hypertension is a prevalent comorbid condition among the older population, and it is an established risk factor for cardiovascular disease, cerebrovascular disease, and chronic kidney disease. However, the prevalence of uncontrolled hypertension among older hypertensive patients on medications is not well-studied. Furthermore, the knowledge about drug adherence patterns among hypertensive patients and factors contributing to nonadherence is the need of the hour to know the burden of the problem. Aims and Objectives: This study aims to determine the prevalence of uncontrolled hypertension among older hypertensive patients, their drug adherence pattern, and factors contributing to nonadherence. Materials and Methods: It was a retrospective, cross-sectional observational study done at the National Centre of Ageing, Guindy, Chennai. Blood pressure (BP) was measured for older hypertensive patients who were on antihypertensive drugs for at least 3 months. Their BP control was assessed. Their drug adherence was assessed using an 8-item MORISKY scale. Results: Study showed prevalence of uncontrolled hypertension to be 61.4%. Uncontrolled hypertension was more among older males (88.2%). Among uncontrolled hypertension, 54.1% were diabetic patients. Among diabetics, 24.7% had one other comorbidity, such as cerebrovascular disease and thyroid disorder. Among uncontrolled hypertension patients, 76.9% had low adherence and 23.1% had high adherence. Women had higher drug adherence than men. Furthermore, adherence was negatively correlated with the duration of hypertension.